2021
DOI: 10.1093/brain/awab103
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cells mediate brain inflammation and neurodegeneration in a mouse model of Parkinson's disease

Abstract: α-synuclein (α-syn), a key pathological component of Parkinson disease (PD), has been implicated in the activation of the innate and adaptive immune system. This immune activation includes microgliosis, increased inflammatory cytokines, and the infiltration of T cells into the central nervous system (CNS). More recently, peripherally circulating CD4 and CD8 T cells derived from individuals with PD have been shown to produce Th1/Th2 cytokines in response to α-syn, suggesting there may be a chronic memory T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 60 publications
7
150
0
2
Order By: Relevance
“…In agreement with this, a recent study demonstrated that αSyn triggers incremental MHC-II expression associated with an accompanying T cell response; therapeutic targeting of T cell disruption in animal models was found to reduce MHC-II expression as well as CNS myeloid cells in relation to αSyn expression. 82 To understand the differential contribution of various peripheral immune cells in synucleinopathy, Iba et al 83 evaluated T lympho-cyte populations in 10-11-month-old transgenic mice overexpressing human αSyn, which demonstrated considerable accumulation of αSyn in the cortical and subcortical regions. The authors found an increase in the number of CD3 and CD4+ T cells in mouse brains, and CD3+ T cells were detected in close proximity to glial cells (Iba1 and GFAP) and human αSyn (SYN211)-positive neurons in the neocortex, hippocampus, and striatum, which supports previous observations in the human brain.…”
Section: Pathological αSyn Triggers Inflammationmentioning
confidence: 99%
“…In agreement with this, a recent study demonstrated that αSyn triggers incremental MHC-II expression associated with an accompanying T cell response; therapeutic targeting of T cell disruption in animal models was found to reduce MHC-II expression as well as CNS myeloid cells in relation to αSyn expression. 82 To understand the differential contribution of various peripheral immune cells in synucleinopathy, Iba et al 83 evaluated T lympho-cyte populations in 10-11-month-old transgenic mice overexpressing human αSyn, which demonstrated considerable accumulation of αSyn in the cortical and subcortical regions. The authors found an increase in the number of CD3 and CD4+ T cells in mouse brains, and CD3+ T cells were detected in close proximity to glial cells (Iba1 and GFAP) and human αSyn (SYN211)-positive neurons in the neocortex, hippocampus, and striatum, which supports previous observations in the human brain.…”
Section: Pathological αSyn Triggers Inflammationmentioning
confidence: 99%
“…Previously, circulating CD4 + and CD8 + T-cells derived from PD patients have been demonstrated to produce Th1/Th2 cytokines in the presence of α -synuclein, suggesting that chronic memory T cell response may exist in PD. In 2021, Williams et al generated an α -synuclein overexpression and T cell-deficient mouse model to elucidate whether α -synuclein aggregation in the midbrain of mice can induce memory T cells to lead to PD [ 90 ]. Indeed, they observed that α -synuclein overexpression upregulates the MHC-II protein level in CNS myeloid cells and induces infiltration of IFN γ -producing CD4 + and CD8 + T cells into the CNS.…”
Section: Pathogenesis Of Pdmentioning
confidence: 99%
“…Many studies have provided evidence that T-cells infiltrate the brain in animal models of Parkinson's disease, including the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model in mouse [10][11][12], 6-hydroxydopamine (6-OHDA) induced neurodegeneration in mice [13] and rats [14], transgenic mice overexpressing the human αSyn (hαSyn, Thy1-SNCA) [15,16], the stereotaxic delivery of adeno-associated viral vectors (AAV) encoding for the wild-type hαSyn in mice [17,18] and rats [19][20][21], and the stereotaxic delivery of AAV encoding for the A53T mutant form of hαSyn in rats [22]. Moreover, several studies have shown that T-cell deficient mice [10,12,23] and rats [21] are significantly protected of neurodegeneration development in animal models of Parkinson's disease, thereby indicating that T-cell response seems to play a fundamental role in this disorder.…”
Section: Role Of T-cells In the Development Of Neuroinflammation And Neurodegeneration Involved In Parkinson's Diseasementioning
confidence: 99%
“…In this regard, Brochard and colleagues [23] observed that Cd4 -/mice but not Cd8 -/mice were protected from MPTP-induced degeneration of dopaminergic neurons of the substantia nigra (SN). In addition, Williams and colleagues [17] recently observed that neurodegeneration of dopaminergic neurons of the SN induced in mice by the stereotaxic deliver of AAV-hαSyn is associated with increased expression of class II MHC on myeloid cells in the CNS and a sharp infiltration of interferon-gamma (IFN-γ) producing CD4 + T-cells and CD8 + T-cells into the SN. Nevertheless, only T-cell receptor (TCR)β or CD4 deficiency, but not CD8 deficiency, attenuated neuroinflammation and neurodegeneration in this mouse model [17].…”
Section: Role Of T-cells In the Development Of Neuroinflammation And Neurodegeneration Involved In Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation